Effect of Light Intensity, Light-Curing Unit Exposure Time, and Porcelain Thickness of IPS e.max press and Vintage LD Press on the Hardness of Resin Cement - Silvia Naliani; Suzan Elias; Rosalina Tjandrawinata (Scientific Dental Journal, 2020)
Background: Porcelain veneer restoration is the primary choice for indirect restoration, especially for anterior teeth, given its high esthetic properties and lower failure rate than resin composites. Glass-based ceramics such as IPS e.max Press and Vintage LD Press are a choice for veneer due to its superior physical properties. Resin cement is used to attach the veneer restoration to the teeth. The polymerization of resin cement used in veneer restoration affects the stability, mechanical properties, and resistance of the restoration. The composition and thickness of the porcelain material affect the light‑curing unit to cured resin cement. Objectives: The aim of this study was to evaluate the influence of porcelain thickness, light intensity, and exposure time in the hardness of resin cement. Methods: Porcelain samples measuring 5 mm in diameter with three types of thicknesses of IPS e.max Press and Vintage LD Press were used in the study. Resin cement in a metal mold was placed under a porcelain sample before curing with a light-emitting diode (LED) intensity of 1300 or 1700 mW/cm2. The hardness test was then carried out on the bottom of the resin cement. Result: The highest hardness value was obtained from a Vintage LD Press with a thickness of 0.7 mm (cured at 1300 mW/cm2 for 20 s). A four‑way ANOVA test showed significant differences for brands, thicknesses, and times of exposure (P < 0.05) as well as insignificant difference for LED intensity. Conclusion: The study indicates that polymerization of resin cement with lower thickness presented higher hardness values. Irradiation time affected hardness, while LED intensity did not.